Preventive medicine of von Hippel-Lindau disease-associated pancreatic neuroendocrine tumors - (:unkn) unknown (BIOSCIENTIFICA LTD, 2018)
Pancreatic neuroendocrine tumors (PanNETs) are rare in von Hippel-Lindau disease (VHL) but cause serious morbidity and mortality. Management guidelines for VHL-PanNETs continue to be based on limited evidence, and survival data to guide surgical management are lacking. We established the European-American-Asian-VHL-PanNET-Registry to assess data for risks for metastases, survival and long-term outcomes to provide best management recommendations. Of 2330 VHL patients, 273 had a total of 484 PanNETs. Median age at diagnosis of PanNET was 35 years (range 10-75). Fifty-five (20%) patients had metastatic PanNETs. Metastatic PanNETs were significantly larger (median size 5 vs 2 cm; P < 0.001) and tumor volume doubling time (TVDT) was faster (22 vs 126 months; P = 0.001). All metastatic tumors were >= 2.8 cm. Codons 161 and 167 were hotspots for VHL germline mutations with enhanced risk for metastatic PanNETs. Multivariate prediction modeling disclosed maximum tumor diameter and TVDT as significant predictors for metastatic disease (positive and negative predictive values of 51% and 100% for diameter cut-off >= 2.8 cm, 44% and 91% for TVDT cut-off of <= 24 months). In 117 of 273 patients, PanNETs > 1.5 cm in diameter were operated. Ten-year survival was significantly longer in operated vs non-operated patients, in particular for PanNETs < 2.8 cm vs >= 2.8 cm (94% vs 85% by 10 years; P = 0.020; 80% vs 50% at 10 years; P = 0.030). This study demonstrates that patients with PanNET approaching the cut-off diameter of 2.8 cm should be operated. Mutations in exon 3, especially of codons 161/167 are at enhanced risk for metastatic PanNETs. Survival is significantly longer in operated non-metastatic VHL-PanNETs.
Keywords: PanNET; von Hippel-Lindau disease; survival; management recommendations; CLINICAL-FEATURES; JAPANESE PATIENTS; GA-68-DOTATOC; SURVEILLANCE; INVOLVEMENT; CRITERIA; PET/CT